Happy hour followed by hangover: financing the UK brewery industry, 1880–1913. Issue 5 (3rd July 2016) - Acheson, Graeme G.; Coyle, Christopher; Turner, John D.
ABSTRACT: In the last 15 years of the nineteenth century c. 300 British brewers incorporated and floated securities on the stock market. Subsequently, in the 1900s, the industry suffered a long-lived hangover. In this article, we establish the stylised facts of this transformation and estimate the gains enjoyed by brewery investors during the boom as well as the losses suffered by investors during the bust of the 1900s. However, not all brewery equity shares suffered alike. We find that post-1900 performance correlates positively with capital-market discipline and good corporate governance and negatively with family control, but does not correlate with indebtedness.